2017
DOI: 10.1083/jcb.201701154
|View full text |Cite
|
Sign up to set email alerts
|

MEIS homeodomain proteins facilitate PARP1/ARTD1-mediated eviction of histone H1

Abstract: PARP1/ARTD1 induces chromatin opening by posttranslational modification of the linker histone H1, but how PARP1 is targeted to physiologically correct gene loci is poorly understood. Hau et al. show that in differentiating neurons, PARP1 is rapidly and specifically recruited to a neuron-specific promoter by the atypical homeodomain protein MEIS2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 53 publications
(103 reference statements)
2
41
1
Order By: Relevance
“…Once differentiation is induced, MEIS associates with chromatin-bound PBX1, it recruits poly-ADP-ribose polymerase 1 (PARP1) and then initiates PARP1-mediated eviction of H1 from chromatin. These findings delineate a sequence of events by which a PBX/MEIS complex facilitates chromatin accessibility of transcriptionally inactive genes in neural progenitor cells (Hau et al 2017). Overall, it has been reported that PBX1 primes genes for activation in different systems and can bind to its target sites when chromatin is still compacted.…”
Section: Partnerships Of Pbc Tfsmentioning
confidence: 57%
“…Once differentiation is induced, MEIS associates with chromatin-bound PBX1, it recruits poly-ADP-ribose polymerase 1 (PARP1) and then initiates PARP1-mediated eviction of H1 from chromatin. These findings delineate a sequence of events by which a PBX/MEIS complex facilitates chromatin accessibility of transcriptionally inactive genes in neural progenitor cells (Hau et al 2017). Overall, it has been reported that PBX1 primes genes for activation in different systems and can bind to its target sites when chromatin is still compacted.…”
Section: Partnerships Of Pbc Tfsmentioning
confidence: 57%
“…Surprisingly, we observed the expression of neurogenic fate determinants already in the NSC (Beckervordersandforth et al , and Table EV1). The qPCR validation of these data showed that neurogenic fate determinants such as MEIS2 (Agoston et al , ; Hau et al , ), SOX11 (Mu et al , ), or PAX6 (Ninkovic et al , ) were already expressed in both activated, EGFR‐positive NSCs (aNSCs) and quiescent, EGFR‐negative NSCs (qNSCs), but virtually absent in diencephalic astrocytes (Figs A and EV1A). The expression levels of these neurogenic fate determinants further increased in the prospectively isolated progeny of NSCs, such as neuroblasts (Figs A and EV1A, and Table EV1; see Beckervordersandforth et al , ; Codega et al , ; Fischer et al , , for the sorting procedure).…”
Section: Resultsmentioning
confidence: 88%
“…To examine how this transcriptional regulation is reflected at the protein level in qNSCs, we used immunohistochemistry (IHC) for two factors following the above described expression pattern: MCM6, a transcription factor regulating proliferation (Noseda & Karsan, ), and MEIS2, regulating neurogenesis in the SEZ (Agoston et al , ; Hau et al , ). We used a long‐term BrdU label‐retaining protocol (Codega et al , ) allowing detection of a subset NSCs and their progeny.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, differential MEIS binding in a specific BAs is generally a very good predictor for matching changes in enhancer activity in the same tissue. Based on our observations and the well-established role of MEIS in transcriptional activation (Choe et al, 2009; Hau et al, 2017; Hyman-Walsh et al, 2010), we propose a model of transcriptional activation, where TALE (MEIS) TFs function as a broad or general activators and HOX paralog selectivity is mainly directed at harnessing TALE functional activity at selected locations. Using their recognition motifs, HOX and/or tissue-specific TFs select specific MEIS binding locations, where they stabilize MEIS binding to generate precise functional outputs, or patterns of enhancer activation (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…7). Interestingly, MEIS2 interacts with PARP1 (Hau et al, 2017), a large enzyme capable of triggering phase condensation (Altmeyer et al, 2015). Increasing MEIS residence time (as a result of the cooperation with HOX and other TFs) may favour PARP1 recruitment at selected loci and, in turn, generate the liquid-liquid phase transitions observed to promote gene activation (Boija et al, 2018; Hnisz et al, 2017).…”
Section: Discussionmentioning
confidence: 99%